ETIKA KOMUNIKASI GURU PENDIDIKAN AGAMA KRISTEN DI TENGAH KEMAJUAN TEKNOLOGI INFORMASI DAN KOMUNIKASI - Yosia Belo; Rika S. (BONAFIDE: Jurnal Teologi dan Pendidikan Kristen, 2023)
The Communication Ethics of Christian Religious Education teachers in the midst of advances in information and communication technology is an urgent topic for research. Because Christian Religious Education teachers need to know the right way to communicate so that they can have a positive and significant impact on every student they teach. By using qualitative methods, especially analyzing related literature, several research results related to this topic were obtained. There are five principles described as follows: prioritizing communication with God, being able to filter any information found and obtained on the internet, using every information technology tool and service always based on the principles of the true Christian faith, upholding wise communication in teaching, and practicing communication that renews and embraces.